49th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2011
DOI: 10.2514/6.2011-220
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Force Generation and Vortex Dynamics of Pitching and Plunging Flat Plates at Low Reynolds Number

Abstract: An experimental investigation of pitching and plunging flat plate at a prescribed effective angle of attack in the St range of 0.16 to 0.32 and k range of 0.5 to 1.0 is presented. Force measurements and PIV technique were used to analyze and quantify the unsteady flow field created by the wing kinematics. A momentumbalance based non-intrusive force measurement technique and a systematic vortex detection algorithm were successfully implemented as a post-processing for PIV data to gain insight on the interplay b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 24 publications
2
23
1
Order By: Relevance
“…The vortex boundary for |Γ 2 | of about 2 can be visualized as an inflection point for Γ 2 in the curve in In summary, the Γ 1 and Γ 2 vortex identification method results can clearly be seen in a paper by Baik et al [33]. In this research, Γ 1 and Γ 2 are used to identify the center of the vortex as well as the vortex bounds for the wake of a pitching and plunging flat plate at low Reynolds numbers.…”
Section: Vortex Identification Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…The vortex boundary for |Γ 2 | of about 2 can be visualized as an inflection point for Γ 2 in the curve in In summary, the Γ 1 and Γ 2 vortex identification method results can clearly be seen in a paper by Baik et al [33]. In this research, Γ 1 and Γ 2 are used to identify the center of the vortex as well as the vortex bounds for the wake of a pitching and plunging flat plate at low Reynolds numbers.…”
Section: Vortex Identification Methodsmentioning
confidence: 68%
“…Baik et al [33] produce a plot in Figure 3.5 that compares the results for the two circulation calculation methods applied to PIV experiments. The calculated values are essentially the same.…”
Section: Methods Of Calculating the Circulation Of A Vortexmentioning
confidence: 99%
“…It was also shown that the development of a larger leading edge vortex was the result of an increase in plunge induced angle of attack. The formation and evolution of these vortical structures and their effects on the force production has been documented in previous studies 1,[4][5][6] . This study will focus on wing flexibility and the resulting fluid-structure interactions.…”
Section: Introductionmentioning
confidence: 80%
“…The method is derived from the incompressible, momentum equation for a Newtonian fluid with the assumption of constant density and dynamic viscosity . The equation governing this can be defined as (5) where is the pressure, is the force per unit volume, is the velocity tensor, and is the Cartesian coordinate tensor. Reynolds decomposition is performed on the component, assuming that the flow is periodic.…”
Section: Force Estimationmentioning
confidence: 99%
“…(5), the force is mainly determined by the quantities on the surface of the control volume. Using the flux equation, Baik et al [28] evaluated the terms in Eq. (5) to identify the contributions from vortical structures and acceleration.…”
Section: B Momentum Form and Flux Form Force Formulasmentioning
confidence: 99%